SUCCESSES AND FAILURES OF ROAD SAFETY POLICY IN EUROPE. (7th October 2012) - Sethi, D; Mitis, F
Abstract : Background: The UN and WHA resolutions on road safety and health and European policy have helped to raise road safety as a health priority. Members States in the WHO European Region are rising to the challenge but there are large inequalities between and within countries in the Region. Purpose: To discuss the successes and failures of road safety policy in Europe. Methods: Survey of health ministry focal persons and age standardised mortality rates. Results: There is almost a 10 fold difference between the country with the highest and lowest age standardised mortality rate in Europe. Variation exists in the implementation of policies around speed control, seat-belt wearing, drink driving, helmet wearing and safer road infrastructure and vehicles. Generally countries in Northwest and Southwest Europe have had more success, with growing success in Central and Eastern Europe, and less success in Southern Europe and the Commonwealth of Independent States. Successful country examples will be discussed. At a European level, there is a correlation between front seat-belt wearing and mortality in car occupants adjusted for car ownership (r=−0.8), implying that successful implementation of this policy saves lives. Similarly there is an association between helmet wearing and deaths in motorcycle riders (r=−0.6). Significance: This paper shows that whereas good progress is being made in road safety in Europe, many countries need to strive for more sustained implementation of policies. Many policies are transferrable; the reasons for the successes and failures of implementation are discussed. More widespread data on reliable indicators are needed.